Factors influencing amblyopia rehabilitation in occlusive therapy - Lança, Carla (2009)
Amblyopia develops in an early period and is a decrease of visual acuity (unilateral or bilateral) caused by a deprivation of vision or abnormal binocular interaction. Prognosis of Amblyopia is better when occlusive treatment is implemented in an early stage. Visual acuity of amblyopic eye does not improve without effective occlusive therapy. The aim of this study is to identify potential risk factors of noncompliance with treatment when it is implemented by parents in amblyopic children.